Hubungan Self-Efficacy Dan Self-Esteem Dengan Kemampuan Interaksi Sosial Siswa-Siswi SMK Garuda - Firli Martanti, Siti; Diel, M. Martono; Pratiwi, Ayu (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Social interaction is a mutual relationship between individuals and groups that affect each other in daily life, that occurs at school shows that there are still students who lack confidence, have low self-esteem and have difficulty communicating with peers, so that their social interaction skills are not optimal. To find out the relationship between self-efficacy and self-esteem and the ability of social interaction between students of SMK Garuda. Sampling technique using total sampling. The sample totaled 127 respondents. Data analysis using the Chi Square correlation test. Based on the results of the study, it was found that the majority of respondents had  high self-efficacy as many as 63 respondents (49.6%), the majority of respondents also had  high self-esteem as many as 78 respondents (61.4%) and the majority of respondents also had sufficient social interaction skills as many as 57 respondents (44.9%). The results of the Chi Square correlation test  obtained a  significant Likelihood Ratio  value between self-efficacy and social interaction ability of 0.028<0.05, so it was said that Ho was rejected and it can be said that there is a relationship  between self-efficacy and social interaction ability and a significant value between self-esteem was also obtained with a social interaction ability of 0.002<0.05, Ho was rejected and it can be said that there is a relationship  between self-esteem and social interaction ability